NIMG-27. THRESHOLD VALUES OF EARLY METABOLIC CHANGES IN 1H MRSI METABOLIC METRICS PREDICTIVE FOR SURVIVAL IN PATIENTS WITH NEWLY DIAGNOSED HIGH-GRADE GLIOMA. (9th November 2020) - Patel, Samir; Wang, Michael; Wachowicz, Keith; Yahya, Atiyah; Murtha, Albert; Amanie, John; Quon, Harvey; Chainey, Jonathan; Ghosh, Sunita; Roa, Wilson
Abstract: BACKGROUND: The purpose of this study was to evaluate the association of specific threshold values for changes in metabolic metrics measured from 1H magnetic resonance spectroscopic imaging (MRSI) to survival of patients with high-grade glioma treated with multimodality therapy. METHODS: Forty-four patients with newly diagnosed high-grade glioma were prospectively enrolled. Serial MRI and MRS scans were performed at baseline, week 4 of radiation therapy (RT), and two months post-RT to measure tumor choline, creatine, and N -acetylaspartate (NAA) normalized to contralateral normal brain. Serial changes in metabolites were assessed using the Wilcoxon signed-rank test. Cox regression analyses adjusted for patient age, KPS, and delivery of concurrent chemotherapy were used to assess the association of changes in metabolic metrics with survival. RESULTS: Median follow-up time was 13.4 years, and vital status was available for 95.1% of patients. Mean normalized choline, creatine and choline/creatine decreased significantly after baseline to post-RT in the overall group of patients (all P < 05). Overall survival (OS) was longer in patients with ≤ 20% increase (vs. > 20%) in normalized choline ( P = .024) or choline/NAA ( P = .024) from baseline to week 4 of RT. During this period, progression-free survival (PFS) was longer in with patients ≤ 40% increase (vs. > 40%) in normalized choline ( P = .013). From mid-RT to post-RT, ≤ 40% decrease (vs. > 40%) in normalized choline/NAA ( P < .001) or choline/creatine ( P = .014), or ≤ 40% increase (vs. > 40%) in NAA/creatine ( P = .030) were associated with reduced median OS. CONCLUSIONS: Threshold values for serial changes in choline metrics on MRSI associated with OS and PFS were identified. These findings suggest a potential clinical role for MRSI to provide an early assessment of treatment response, and could enable risk-adapted therapy in clinical trial development and clinical practice.